The association between peer‐victimisation and structural and functional brain outcomes: A systematic review. Issue 2 (12th May 2022) - Ke, Tianyuan; De Simoni, Sara; Barker, Edward; Smith, Patrick
Abstract: Background: Peer adversity and aggression are common experiences in childhood and adolescence which lead to poor mental health outcomes. To date, there has been no review conducted on the neurobiological changes associated with relational peer‐victimisation, bullying and cyberbullying. Methods: This systematic review assessed structural and functional brain changes associated with peer‐victimisation, bullying, and cyberbullying from 1 January 2000 to April 2021. A systematic search of Psychoinfo, Pubmed, and Scopus was performed independently by two reviewers using predefined criteria. Twenty‐six studies met the selection criteria and were considered for review. Results: The data collected shows altered brain activation of regions implicated in processing reward, social pain, and affect; and heightened sensitivity and more widespread activation of brain regions during acute social exclusion, most notably in the amygdala, left parahippocampal gyrus, and fusiform gyrus, associated with victimisation exposure. In addition, victimised youths also demonstrated greater risk‐taking behaviours following acute social exclusion showing greater ventral striatum—inferior frontal gyrus coupling, activation in the bilateral amygdala, orbital frontal cortex (OFC), medial prefrontal cortex (MPFC), temporoparietal junction (TPJ), medial posterior parietal cortex (MPPC) and dorsomedial prefrontal cortex (dmPFC), suggesting greater social monitoring, seeking of inclusion, and more effortful cognitive control. The studies included participants from a very broad developmental age range, mostly using cross‐sectional measure of peer‐victimisation exposure, at varying developmental stages. Conclusions: This review highlights the need for more neuroimaging studies in cyberbullying, as well as longitudinal studies across more diverse samples for investigating gender, age, and developmental interactions with peer‐victimising. This also brings to attention the importance of addressing bullying victimisation particularly in adolescence, given the evidence for social stress in heightening developmentally sensitive processes which are associated with depression, anxiety, and externalising symptoms.